Sikap Kritikus Hadis terhadap Periwayat Ahli Bid’ah - Isnaeni, Ahmad (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2011)
A Study of heretics related to hadith naration is interesting, because hadith is a source of Islamic law which should be flawles. Besides, it had been a topic of discussion among muslim scholars (ulama). We can even find the heretics in shahih al-Bukhari dan shahih Muslim. Significance to discuss this topic is due to the polemic of the term it self. The polemic can be seen from the meaning of “ahl al-ahwa wa al-bida’ “ which is negatif connotation. The historical Reality tells us that the muslim scholars have always been in neutral position to appraise the narration of hadith from those accused heretics. They are divided in two categories: the first is the infidels and the consequence is the unacceptability of their narration of hadith. The second category is the sinners. The narration of the sinners falls under two classifications; they are propagandist (da’iyah) and nonpropagandist (ghairu da’iyah). The first group’s narration is unacceptable which the second group’s narration depends on the individual credibility of the narrator.